Speaking of Feminism : Today's Activists on the Past, Present, and Future of the U.S. Women's Movement - Seidman, Rachel Filene (Book collections on Project MUSE., 2019)
"From the Women's Marches to the MeToo movement, it is clear that feminist activism is still alive and well in the twenty-first century. But how does a new generation of activists understand the work of the movement today? How are their strategies and goals unfolding? What worries feminist leaders most, and what are their hopes for the future? In Speaking of Feminism, Rachel F. Seidman presents insights from twenty-five feminist activists from around the United States, ranging in age from twenty to fifty. Allowing their voices to take center stage through the use of in-depth oral history interviews, Seidman places their narratives in historical context and argues that they help explain how recent new forms of activism developed and flourished so quickly. These individuals'compelling life stories reveal their hard work to build flexible networks, bridge past and present, and forge global connections. This book offers essential reading for anyone seeking to understand the contemporary American women's movement in all its diversity."--EBSCO